PENGARUH BRAND AMBASSADOR TERHADAP BRAND IMAGE PRODUK WARDAH PADA MAHASISWA POLITEKNIK NEGERI UJUNG PANDANG - Siti Raihanah; Syahriah Sari; Ahmadi Usman (Jurusan Administrasi Niaga, Politeknik Negeri Ujung Pandang, 2021)
This study aims to determine the effect of brand ambassador of brand image of wardah products used by students of Politeknik Negeri Ujung Pandang. The problem of this study is that some students feel wardah’s brand ambassadors have not influenced them to use the wardah products. The study is conducted in Politeknik Negeri Ujung Pandang. Based on purposive sampling method, a total number of sample is 83 students of business administration department. Interviews and questionnaire was used to get the data of this study. This study showed that brand ambassador impact significantly brand image of wardah products for students of business administration department. The determination coefficient of this study is 0,36% meaning that the percentage of brand ambassador affects brand image at 36%, while 74% of brand image are influenced by other variables.